The book of dreams eaudiobook Dream (bunn) series, book 1. - Bunn, Davis (Book of Dreams, 2012)
Three-time Christy Award winner Davis Bunn has sold more than six million copies of his books. In Book of Dreams, psychiatrist Dr. Elena Burroughs begins treating a mysterious woman. Elena soon becomes convinced that ominous forces are at work in the woman's life, leading her to question how a person can truly understand-and fulfill-the will of God. ". a suspenseful thriller with well-drawn characters and a touch of the paranormal."-Library Journal